2020
DOI: 10.1016/j.rmed.2020.105877
|View full text |Cite
|
Sign up to set email alerts
|

Time-to-death in chronic respiratory failure on home mechanical ventilation: A cohort study

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…In a European survey, patients treated with TPPV represented 13% of the population on long-term mechanical ventilation [82], with a wide variability from country to country. In a British study of all-cause mortality of 1,210 patients under HMV over a 10-year period, patients using TPPV represented 12% of the deceased [214]. A similar proportion of TPPV in HMV has been reported in Canada [215].…”
Section: Special Situationsmentioning
confidence: 74%
See 2 more Smart Citations
“…In a European survey, patients treated with TPPV represented 13% of the population on long-term mechanical ventilation [82], with a wide variability from country to country. In a British study of all-cause mortality of 1,210 patients under HMV over a 10-year period, patients using TPPV represented 12% of the deceased [214]. A similar proportion of TPPV in HMV has been reported in Canada [215].…”
Section: Special Situationsmentioning
confidence: 74%
“…TPPV is associated with the risk of specific complications such as life-threatening – although rare – tracheal bleeding, ventilator-associated pneumonia, obstructive mucus plugging or tracheal granuloma formation and stenosis that may increase morbidity and mortality compared to NIV [224-226]. Data on outcomes of long-term tracheostomy ventilation come from cohort studies but have not been systematically analyzed and compared to NIV in a conclusive way [214, 215, 227, 228].…”
Section: Special Situationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the series analyzed (table 4) the percentage of patients invasively ventilated through tracheostomy (TIV) varies between 3.1% and 12.4% (25,23,8,26) whereas in our cohort it was only 5.24%, this difference may be a consequence of the fact that in the Canadian program the most frequent diagnosis was NMD (30.4%) while the English cohort reported that it had 21.6% of patients with a diagnosis of ALS (26).…”
Section: Discussionmentioning
confidence: 52%
“…In 2020, Schwarz et al analyzed the time elapsed from admission to death of 1,210 patients on HMV in England and described that patients with ALS had the lowest mean survival, of 7 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) months, whereas patients with OHS on HMV had the longest survival, 33 (13-75) months, and the mean survival of the overall cohort was 19.5 months; in addition, 150 patients (12.4%) were ventilated through tracheostomy (26). The Swedish group describes that of its 1526 patients, only 6% were ventilated through tracheostomy and that the worst survival was observed in patients with ALS, with 20% survival at 2 years and 5% at 5 years (25).…”
Section: Discussionmentioning
confidence: 99%